Pseudomystus tuberosus, a new species of catfish from central Borneo (Actinopterygii: Bagridae) - Ng, Heok Hee; Tan, Heok Hui (Zootaxa, 2024)
Pseudomystus tuberosus, a new species of bagrid catfish from the Kahayan River drainage in south central Borneo, is described in this study. It can be distinguished from all congeners in having a strongly humped dorsal profile (vs. dorsal profile weakly humped or without hump), as well as its head and flanks covered with rounded tubercles (vs. smooth or with capillaceous epithelial projections). Pseudomystus tuberosus most closely resembles P. vaillantii, but can be further distinguished from it in having a smaller eye (8% HL vs. 9–12) and a slenderer caudal peduncle (5.5–6.0% SL vs. 6.8–8.1). The identity of P. carnosus, described from southern Sumatra, is also discussed, and the species treated as a junior synonym of P. moeschii.